Pemodelan Solidifikasi untuk Proses Pembekuan Air dengan Geometri Cetakan Es Bujur Sangkar dan Persegi Panjang - Andreas Pujianto; Prabowo Prabowo; Sigit Deddy P. Sidhi (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2016)
Numerical study is presented concerning transient solidification for water freezing process. The ice can produces 25 kg of ice block product is used as model in this study. 2D-simpllified geometry of ice can is modeled with square and rectangular shape which have different aspect ratio (H/L) 1 and 0.62 respectively. Both of shapes is compared one to another based on heat transfer and duration of solidification. Boundary conditions use isothermal temperature walls. Three walls (top, bottom, and right) have the same temperature values are -8℃ and the left wall temperature value is 0℃. Second order implicit URANS equations were solved with laminar model in numerical calculation. Most of internal heat energy (latent and sensible) from the water released to the walls which have lower temperature than other wall for 15 hours cooling process. This condition makes temperature of the liquid water decrease and phase change occured. The rectangular shape perform better than the square shape in heat transfer of internal heat energy from the water to the walls shape. The top and bottom wall from rectangular shape have greater value of heat transfer because their area are larger than other walls. Solidification process of the water in the rectangular shape faster 7,03% than square which showed by growth of water solid fraction in time of 15 hours cooling process.